THE EFFECTIVE NEGOTIATION METHODS FOR RESOLVING BUSINESS PROBLEMS - Asrindah Nst; Buyung Solihin Hasugian; Tamara Salsabila (Universitas Dharmawangsa Medan, 2023)
ABSTRACTBusiness conflicts are unavoidable and can occur in various situations. Effective negotiation can be a powerful tool for resolving business conflicts and reaching solutions that are beneficial for all parties. I looked for various effective negotiation strategies that we can use to resolve business conflicts in this research .First, we talked about how important effective communication and an open approach are in negotiations. Clear and transparent communication allows the parties to understand what they need to reach a mutually beneficial agreement. Secondly, I emphasize how important it is to build good relationships between all parties involved in negotiations. Have solid and trust in each other can help reduce tensions and open up opportunities for both to work together to find solutions.Keywords: Negotiation Techniques, Conflict in business, Business Negotiations.